Dryland Fodder Radish Genotypes: Planting Date Effects on Nutritive Value and In-Vitro Dry Matter Degradability in Midlands of KwaZulu-Natal, South Africa - Lwando Mbambalala; Thamsanqa Doctor Empire Mpanza; Tlou Julius Tjelele; Lusanda Ncisana; Sphesihle Mkhungo; Lucky Sithole; Mpho Siennah Nzeru; Patrick Ngwako Rakau; Zikhona Theodora Rani-Kamwendo; Ntuthuko Raphael Mkhize (Grasses)
Erratic rainfall and extended dry periods challenge forage production and livestock feed sustainability in dryland agriculture regions. This study investigated the effects of planting dates and genotype selection on the nutritive value and in-vitro dry matter degradability (IVDMD) of fodder radish genotypes in Midlands of KwaZulu-Natal, South Africa. The experiment followed a completely randomised design with three fodder radish genotypes (Endurance, Line 2, and Nooitgedacht) and five planting dates (December, January, February, March and May). After three months of growth in each planting date, crops were harvested, prepared and analysed for various nutritional parameters including crude protein, fibre content, and IVDMD. Results revealed that December had the highest crude protein (28–31%) across genotypes, while March plantings optimised total non-structural carbohydrates (13.31%) and metabolisable energy (6.64 MJ/kg). The Nooitgedacht genotype demonstrated improved performance, achieving higher IVDMD of 85.54% for leaves in December plantings and 77.51% for tubers in February plantings. Significant interactions between planting dates and genotypes were observed for ash, crude protein, and cellulose in leaves. In conclusion, these findings highlight the crucial role of planting date selection and genotype choice in optimising fodder radish production under dryland conditions, offering valuable insights for enhancing livestock productivity and supporting sustainable rural livelihoods.